Spread of TEM, VIM, SHV, and CTX-M β-Lactamases in Imipenem-Resistant Gram-Negative Bacilli Isolated from Egyptian Hospitals - El sayed Hamdy Mohammed; Ahmed Elsadek Fakhr; Hanan Mohammed El sayed; Said abd Elmohsen Al Johery; Wesam Abdel Ghani Hassanein (International Journal of Microbiology)
Carbapenem-resistant Gram-negative bacilli resulting from β-lactamases have been reported to be an important cause of nosocomial infections and are a critical therapeutic problem worldwide. This study aimed to describe the prevalence of imipenem-resistant Gram-negative bacilli isolates and detection of blaVIM, blaTEM, blaSHV, blaCTX-M-1, and blaCTX-M-9 genes in these clinical isolates in Egyptian hospitals. The isolates were collected from various clinical samples, identified by conventional methods and confirmed by API 20E. Antibiotic susceptibility testing was determined by Kirby-Bauer technique and interpreted according to CLSI. Production of blaVIM, blaTEM, blaSHV, and blaCTX-M genes was done by polymerase chain reaction (PCR). Direct sequencing from PCR products was subsequently carried out to identify and confirm these β-lactamases genes. Out of 65 isolates, (46.1%) Escherichia coli, (26.2%) Klebsiella pneumoniae, and (10.7%) Pseudomonas aeruginosa were identified as the commonest Gram-negative bacilli. 33(50.8%) were imipenem-resistant isolates. 22 isolates (66.7%) carried blaVIM, 24(72.7%) had blaTEM, and 5(15%) showed blaSHV, while 12(36%), 6(18.2%), and 0(0.00%) harbored blaCTX-M-1, blaCTX-M-9, and blaCTX-M-8/25, respectively. There is a high occurrence of β-lactamase genes in clinical isolates and sequence analysis of amplified genes showed differences between multiple SNPs (single nucleotide polymorphism) sites in the same gene among local isolates in relation to published sequences.